Aplicación de los mapas mentales en la comprensión lectora en estudiantes del ciclo I de instituciones de educación superior - Pizarro Cherre, Edwin Fernando (2008)
-- This investigation has as main aim to determine the influence of the application of the Mind Maps in the reading comprehension. For it apply the Cloze Test to be able to measure the reading comprenhension in a group of 209 students of superior education of wich 104 use de Mind Maps as technique of reading. The Cloze Test is composed of 6 subtest of 20 items each one developed by Raul Gonzáles Moreyra in an investigation on the level of readin comprehension in 1998 applied to university students. The experimental group was evaluated in the use of the Mind Maps applying a didactic instrument proposed by Jasmin Sambrano The result show us that in both groups the level of reading comprehension es deficient and in no casa would reach the level of independent reading. however is observed that group that applies the Mind Map improves its levels of reading comprhension percentage disminishing the precentage of terrible and bad readers. Of this way; it concludes showing the influence of the Mind Maps in the reading comprehension coinciding with the students of Dr. Taul Gonzales Moreyra as for establishing that the level of reading comnprehension coinciding with the investigation of Raul Gonzales Moreyra as for estableshing that the level of reading comprehension in our estudents is low ant deficient.